CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, GREEN INNOVATION AND CORPORATE PROFITABILITY - Marietza, Fenny (Jurnal Akuntansi, 2023)
This study examines the effect of corporate social responsibility disclosure and the application of green innovation on corporate profitability. The population of this study is all companies engaged in energy and mining listed on the Indonesia Stock Exchange in 2018-2021. The sample in this study was energy and mining companies that provided annual and sustainability reports consecutively during the research period. The analysis tool used in this study is E-views version 12. The results of this study show that CSR disclosure does not positively affect profitability proxied using ROA, ROE, and EPS. In contrast, green innovation positively influences the company’s ROE. It does not positively affect the company's ROA and EPS, which means that the disclosure of green innovation What the company does can attract investors to invest and invest in the company.